Adapting to an invasive species: Toxic cane toads induce morphological change in Australian snakes - Phillips, Ben L. (National Academy of Sciences, 2004)
The arrival of invasive species can devastate natural ecosystems, but the long-term effects of invasion are less clear. If native organisms can adapt to the presence of the invader, the severity of impact will decline with time. In Australia, invasive cane toads (Bufo marinus) are highly toxic to most snakes that attempt to eat them. Because snakes are gape-limited predators with strong negative allometry for head size, maximum relative prey mass (and thus, the probability of eating a toad large enough to be fatal) decreases with an increase in snake body size. Thus, the arrival of toads should exert selection on snake morphology, favoring an increase in mean body size and a decrease in relative head size. We tested these predictions with data from specimens of four species of Australian snakes, collected over >80 years. Geographic information system layers provided data on the duration of toad exposure for each snake population, as well as environmental variables (latitude, precipitation, and temperature). As predicted, two toad-vulnerable species (Pseudechis porphyriacus and Dendrelaphis punctulatus) showed a steady reduction in gape size and a steady increase in body length with time since exposure to toads. In contrast, two species at low risk from toads (Hemiaspis signata and Tropidonophis mairii) showed no consistent change in these morphological traits as a function of the duration of toad exposure. These results provide strong evidence of adaptive changes in native predators as a result of the invasion of toxic prey.